Sentimentalist Practical Reason and Self-Sacrifice. Issue 3 (27th May 2018) - Slote, Michael
ABSTRACT: For obvious reasons sentimentalists have been hesitant to offer accounts of moral reasons for action: the whole idea at least initially smacks of rationalist notions of morality. But the sentimentalist can seek to reduce practical to sentimentalist considerations and that is what the present paper attempts to do. Prudential reasons can be identified with the normal emotional/motivational responses people feel in situations that threaten them or offer them opportunities to attain what they need. And in the most basic cases altruistic/moral reasons involve the empathic transfer of one person's prudential reasons and emotions to another person or persons who can help them. Practical/moral reasons for self-sacrifice also depend on empathic transfer and can vary in strength with the strength of the transfer.